2021
DOI: 10.7181/acfs.2021.00269
|View full text |Cite
|
Sign up to set email alerts
|

Use of a buccinator myomucosal flap and bilateral pedicled buccal fat pad transfer in wide palatal fistula repair: a case report

Abstract: Primary palatoplasty for cleft palate places patients at high risk for scarring, altered vascularity, and persistent tension. Palatal fistulas are a challenging complication of primary palatoplasty that typically form around the hard palate–soft palate junction. Repairing palatal fistulas, particularly wide fistulas, is extremely difficult because there are not many choices for closure. However, a few techniques are commonly used to close the remaining fistula after primary palatoplasty. Herein, we report the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 15 publications
(22 reference statements)
0
4
0
Order By: Relevance
“…Over the last two decades, the FAMMIF has found multiple useful applications in the reconstruction of defects in the head and neck area. These are not limited to cancer surgery but also to post‐traumatic defects and to the rehabilitation of cleft lip and palate patients 12,13 . Undoubtedly, due to its anatomical and tissue characteristics, this flap is ideal for the oropharynx, floor of mouth and tongue reconstruction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the last two decades, the FAMMIF has found multiple useful applications in the reconstruction of defects in the head and neck area. These are not limited to cancer surgery but also to post‐traumatic defects and to the rehabilitation of cleft lip and palate patients 12,13 . Undoubtedly, due to its anatomical and tissue characteristics, this flap is ideal for the oropharynx, floor of mouth and tongue reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…These are not limited to cancer surgery but also to post‐traumatic defects and to the rehabilitation of cleft lip and palate patients. 12 , 13 Undoubtedly, due to its anatomical and tissue characteristics, this flap is ideal for the oropharynx, floor of mouth and tongue reconstruction. In particular, the FAMMIF is indicated in the reconstruction of small to moderate defects (post T1‐T2 tumors resection) when single functional units are involved.…”
Section: Discussionmentioning
confidence: 99%
“…This variety in harvesting techniques and flap thickness offers a broad field of application in tension-free, watertight, and localised defect closure. Apart from its traditional indication for primary closure of wide palatal clefts or as a backup procedure for palatal lengthening in velopharyngeal dysfunction, many case reports on the topic have been published [ 15 , 16 ]. In 1989, Bozola et al reported a cadaver and clinical study on the axial patterned buccinator musculomucosal flap, which had been successfully applied not only in cleft surgery but also in tumour surgery and osteomyelitis [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…It offers an ample amount of tissue for effective defect coverage, making it a reliable choice for medium-sized defects [26]. One of its distinguishing features is the potential for mucosa-to-mucosa replacement, facilitating optimal functional and aesthetic outcomes [27]. Moreover, BMF is associated with relatively low morbidity and yields optimal functional and cosmetic results [27,28 ▪ ].…”
Section: Treatment Options For Massive Palatal Defects Following Pala...mentioning
confidence: 99%